Simulation analysis of the switching of 230kV substation shunt capacitor banks with a 6% series reactor for limiting transient inrush currents and oscillation overvoltage - Patcharoen, Theerasak; Ngaopitakkul, Atthapol; Pothisarn, Chaichan; Leelajindakrairerk, Monthon (My University, 2018)
This paper presents the simulation and investigation of switching large shunt capacitor banks in a 230kV Thailand substation system. Simulations are performed using PSCAD/EMTDC to determine the peak of the transient inrush currents, the oscillation overvoltage and the frequency of the inrush current. The inrush current is generated by energizing the 4 × 72 Mvar, 230kV shunt capacitor banks. The purpose is to observe and investigate the behaviour of transient inrush currents and oscillation overvoltages to ensure the safe and successful operation of shunt capacitor banks. The methodology of inrush current transient analysis and transient reduction control was studied. The proposed method for controlling system transients during capacitor energization is through the use of a switching shunt capacitor bank with a series 6% reactor. The simulation cases for transient mitigation are numerically conducted for six different cases: a base case, with a pre-insertion resistor, with a pre-insertion inductor, with a current-limiting reactor, with a series 6% reactor and using synchronous closing control. The effects of parameters such as the sizing of the current-limiting reactor, the capacitor bank rating and the short-circuit impedance of the system are investigated. The simulation results demonstrate that the switching shunt capacitor bank with a series 6% reactor is effective in reducing the high transient inrush currents and oscillation overvoltages.
Keywords: 6% reactor; Back-to-back capacitor switching; Current-limiting reactor; Inrush current; Oscillation overvoltage; Shunt capacitor bank; Switching transients